Studies on the components of the contact phase system in patients with acute nonlymphoblastic leukemia - Annichino-Bizzacchi , Joyce Maria; Arruda, Valder Roberval; Machado, Tania Fátima Gomes; Gallizoni, Andrea Maria; Ribeiro, Cristina Cedran (São Paulo Medical Journal, 1997)
The objective of the present study was to evaluate factors of the plasma kallikrein system in patients with acute nonlymphoblastic leukemia (ANLL), and compare the results to a normal control group. A prospective study was performed in the Tertiary Health Care Institution, Hemocentro, Campinas State University, Campinas, São Paulo, Brazil. Thirty-five patients, diagnosed as ANLL between 1988 and 1991, were considered for participation. Eleven patients were not elegible, according to the exclusion criteria: infection/ septicemia, previous treatment or blood transfusion. The study was performed with 24 ANLL patients, average age 34 years (16-69 years), 14 men and 10 women. Nineteen healthy volunteers, workers from the Hematology Center, average age 32 years (21-59 years), 11 men and 8 women, were the control group. Plasmatic prekallikrein, C1-inhibitor, alpha 2-macroglobulin, activated partial thromboplastin time, prothrombin time, factor XII, factor XI, factor V and prealbumin were measured. Plasmatic prekallikrein (p=0.02) and prealbumin (p=0.03) were significantly decreased, and prothrombin time increased (p=0.003) in the patient group when compared to the control. Significant correlation (r=0.49, critical value=0.43, p<0.05) between prekallikrein and prealbumin, and between prothrombin time and factor V (r=0.54, critical value=0.44, p<0.05) was demonstrated in the patient group. No correlation was found between parameters analysed and circulant blast count or leukemia subgroups. Statistical analysis was performed by theWilcoxon test. Correlation between the parameters was also verified. These results suggest activation of the contact system or impaired liver synthesis in patients with ANLL, and could contribute to disease complications.